Analyzing the Association HbA1c control by Depression, social participation and Utilizing Self-management Questionnaire. (July 2019) - Liu, Yun-Ting; Lin, Li-Ying; Tuan, Chi-Wei; Yang, Chun-Ying; Tang, Pei-Ling
Highlights: This study investigated the factors affecting the effectiveness of HbA1c control aged >65 years. The effectiveness increased with age and was better among those who received education, lived alone. Revealed that the people living with the patients affected the effectiveness of HbA1c control in the patients. Members living with patients should co-participate in self-management education courses. Abstract: Aims: In Taiwan, 24.7% of the population aged ≥65 years has been diagnosed with type 2 diabetes. Only 23% of diabetes patients effectively conduct self-management. This study focused on the effects of self-management among type 2 diabetes patients aged ≥65 years on the effectiveness of their HbA1c control. Methods: This cross-sectional study enrolled patients aged ≥65 years with type 2 diabetes who were admitted to a metabolic clinic at a medical center and treated over six months. 192 patients were recruited, and data were recorded using structured questionnaires. The HbA1c level of the recruited subjects was measured for statistical analysis. Results: Older age, education, living alone, and an above-average level of self-management were associated with increased HbA1c control effectiveness; patients who used insulin had worse HbA1c control effectiveness. Conclusion: That cohabitants living with diabetes patients affected the effectiveness of HbA1c control, suggesting that family members should also participate in self-management education programs. Given the advances in information networks, a lively and interactive mode of health education animation for uneducated diabetes patients should be developed, and medical teams should be encouraged to establish a two-way communication channel with patients improve the effectiveness of HbA1c control in diabetes patients aged >65 years.